Socialist third World : urban development and territorial planning / edited - "Forbes, Dean (ed.) ; Thrift.Nigel (ed.)" (New York, 1987)
The socialist Third World countries have grown from a handful in the 1950s to over thirty in the 1980s, yet they have received little attention in the development literature. The essays in this volume examine the territorial planning experience of several key socialist countries: Algeria, Cuba, Guyana, Nicaragua, Vietnam, PDR Yemen, Zimbabwe. Territorial considerations are now of great importance in the economic and social planning of the characteristically centrally planned countries under scrutiny. The pressure for industrialization, the equitable distribution of growth and benefits, and national defence produce economic problems that in some cases are staved off by recourse to international borrowing. Contradictory stresses such as these are resolved in different ways by different countries, and these essays describe the various approaches and policies employed in each of the nations examined.
Keywords: Socialism developing countries